2015
DOI: 10.3168/jds.2014-8515
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Lactobacillus strains for their ability to produce conjugated linoleic acid in milk and to adhere to the intestinal tract

Abstract: Conjugated linoleic acid (CLA) has been shown to provide beneficial effects on health; however, the amount consumed in food is far from that required for the desired effects. Thus, increasing the CLA content in dairy foods through milk fermentation with specific lactic acid bacteria (LAB) offers an interesting alternative. Moreover, some LAB may be able to adhere to the intestinal mucosa and produce CLA through endogenous synthesis. Therefore, the objective of this study was to screen LAB isolates for their ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…The two isomers that have been shown to have bioactive potential are cis -9, trans -11 ( c 9, t 11) and trans -10, cis -12 ( t 10, c 12). The health-promoting properties of CLA include anticarcinogenic, antiatherogenic, anti-inflammatory, and antidiabetic activity, as well as the ability to reduce body fat (Sosa-Castañeda et al, 2015). Although it is a native component of milk, the amount consumed in foods is far from that required in order to obtain desired beneficial effects.…”
Section: Biofunctional Foodsmentioning
confidence: 99%
“…The two isomers that have been shown to have bioactive potential are cis -9, trans -11 ( c 9, t 11) and trans -10, cis -12 ( t 10, c 12). The health-promoting properties of CLA include anticarcinogenic, antiatherogenic, anti-inflammatory, and antidiabetic activity, as well as the ability to reduce body fat (Sosa-Castañeda et al, 2015). Although it is a native component of milk, the amount consumed in foods is far from that required in order to obtain desired beneficial effects.…”
Section: Biofunctional Foodsmentioning
confidence: 99%
“…Recently, Terán et al (2015) examined 64 food-grade lactobacilli for CLA isomers production and revealed that only 04 L. plantarum strains were able to synthesize CLA isomers from LA which is lower than the 03 L. plantarum strains (HIF15, HIF64, HIF128) reported in present study. In another recent study Sosa-Castañeda et al (2015) assessed the CLA production abilities of 13 Lactobacillus strains out of which strain L. fermentum J20 produced more c9, t11 (42.63 ± 0.91 lg/ml) and t10, c12 (8.27 ± 0.64 lg/ml) CLA isomers then reported in present investigation. By contrary, the production of c9, t11(7.73 ± 0.52 lg/ml) isomer by another L. fermentum strain J23 is lower while that of t10, c12 (11.25 ± 0.51 lg/ml) is higher than L. fermentum strains reported here.…”
Section: Cla Isomers Analysis By Gcmentioning
confidence: 99%
“…Therefore, microbial CLA uptake in humans is visualized as the most purposeful strategy. CLA producers have the ability to crosslink with adipocytes cell lines in vitro and gut epithelial cells in human and animal model (Sosa-Castañeda et al 2015). Moreover, in an in vitro study Dahiya and Puniya (2015) reported that CLA producing strains had good probiotic-to-functional attributes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations